LEFT UPPER LOBE PULMONARY VEIN TRAVERSING THE LEFT OBLIQUE FISSURE-A RARE, UNSEEN ANATOMIC VARIANT - Choudhury, Priyam; Mohapatra, Ashutosh; Parekh, Maansi R; Donuru, Achala (Journal of Ayub Medical College Abbottabad, 2018)
A 38-year-old African American male patient presented to the emergency department with complaints of shortness of breath for 1 hour. The patient was a crack cocaine addict. His physical examination revealed findings consistent with shortness of breath but the chest X-rays picture was unusual. A CT scan of the chest revealed left upper lobe superior pulmonary vein crossing the left oblique fissure and draining into the left atrium which is a deviant from the usual normal anatomy and unreported till now. Keywords: Left pulmonary vein; Left Oblique fissure; anatomic variant